Pengaruh Kombinasi NPK Dan Pupuk Kotoran Bebek Terhadap Pertumbuhan Dan Hasil Tanaman Sorgum Di Tanah Gambut - Andria, Mega; Abdurrahman, Tatang; Rahayu, Sri (Jurnal Sains Mahasiswa Pertanian, 2020)
The study aims to determine the effect of the combination of NPK and fertilizar duck manure on the growth and yield of sorghum in peat soil. The research was conducted at sepakat II street, Mapar aley, South east Pontianak sub-district. Starting from December until march, 2019. The study design (CRD) used a completely randomized design with 6 treatments which were repeated 4 times. The treatment is as follows: A = 100% NPK fertilizer is equivalent 400 kg/ha, B = 80% NPK fertilizer is equivalent to 320 kg/ha +20% duck manure equivalent to tons/ha, C = 60% NPK fertilizer is equivalent to 240 kg/ha +40% duck manure equivalent to 6 ton/ha, D = 40% NPK fertilizer is equivalent to 160 kg/ha +60% duck manure equivalent to 9 tons/ha, E = 20% NPK fertilizer is equivalent to 80 kg/ha + 80% duck manure equivalent to 12 tons/ha, F = 100% duck manure equivalent to 15 tons/ha. The variables that observed in this study were plant height, number of leaves, stem diameter, root volume, weight of plant dry, weight of 1,000 seeds, seed weight per panicle. The results showed that the distributing of a combination of NPK fertilizer and duck manure to the growth and yield of sorghum in peat soil had increased root volume and plant height aged 3,5 MST. In general the combination of NPK and fertilizar duck manure influence the growth and yield of sorghum in peat soil. Keywords: duck manure, NPK, peat and sorghum.